What about thematic information? An analysis of the multidimensional visualization of individual mobility - Menin, Aline; Quere, Clément; Wagner, Jorge; Chardonnel, Sonia; Davoine, Paule-Annick; Stuerzlinger, Wolfgang; Freitas, Carla Maria Dal Sasso; Nedel, Luciana; Winckler, Marco (Visual informatics (Online), 2025)
This paper reviews the literature on the visualization of individual mobility data, with a focus on thematic integration. It emphasizes the importance of visualization in understanding mobility patterns within a population and how it helps mobility experts address domain-specific questions. We analyze 38 papers published between 2010 and 2024 in GIS and VIS venues that describe visualizations of multidimensional data related to individual movements in urban environments, concentrating on individual mobility rather than traffic data. Our primary aim is to report advances in interactive visualization for individual mobility analysis, particularly regarding the representation of thematic information about people’s motivations for mobility. Our findings indicate that the thematic dimension is only partially represented in the literature, despite its critical significance in transportation. This gap often stems from the challenge of identifying data sources that inherently provide this information, necessitating visualization designers and developers to navigate multiple, heterogeneous data sources. We identify the strengths and limitations of existing visualizations and suggest potential research directions for the field. •Analysis of 38 visual analytics solutions designed to aid the exploration of individual mobility data across spatial, temporal, and thematic dimensions.•An analysis of how visualization tools incorporate the theme dimension and which thematic properties are addressed.•Analysis of how the subject is approached within GIS and VIS communities. [Display omitted]